Preliminary Exploration of Natural Polyphenols and/or Herbal Mix Replacing Sodium Nitrate to Improve the Storage Quality of Pork Sausage - Angeliki-Niki Kaloudi; Agori Karageorgou; Michael Goliomytis; Panagiotis Simitzis (Applied Sciences)
Synthetic agents are regularly used as preservatives in pork meat products such as sausages. However, these compounds can be harmful to human health, due to their carcinogenic potential. As a result, natural antioxidants derived from herbs and medicinal plants are continuously and thoroughly assessed to replace/minimize the application of synthetic agents during meat processing and storage. The current study was consequently implemented to highlight the effects of natural polyphenols and/or an herbal mix on the quality characteristics of pork sausages. Five batches of sausages were manufactured using the same recipe and raw materials; the control, without sodium nitrate and natural preservatives (CON), and four groups supplemented with sodium nitrate at 0.015% (SN), olive polyphenols at 0.2% (POL), an herbal mix containing rosemary, savory, camelia, thyme, lemon balm and turmeric at 0.2% (NM), or the concomitant addition of olive polyphenols (0.1%) and the herbal mix (0.1%) (POL + NM). Assessment of pH, color, cooking loss, tenderness and oxidative stability was implemented immediately after the manufacture of the sausages (day 0) and at 1, 2 and 3 months after refrigerated storage. It was illustrated that the oxidative stability of sausages was ameliorated as a consequence of POL or/and NM addition, since the values of malondialdehyde (MDA) were significantly decreased compared to the control (p < 0.001) at months 1, 2 and 3, and the values were similar to those observed in the SN group that served as a positive control. Values for the lightness (L), shear force and cooking loss were similar among the experimental treatments (p > 0.05). On the other hand, pH values were greater in the SN and NM groups than in the other groups (p < 0.05). Redness (a*) was significantly higher in the SN group and yellowness (b*) in the NM and POL + NM groups compared to the other groups (p < 0.001). It can be concluded that the examined polyphenols and/or herbal mix could be used as an alternative to nitrates for the amelioration of oxidative stability in pork sausages.